Playground Settings and the Impact of Recess on Classroom Attention - Peterson, Christine (My University, 2010)
This study focuses on the comparison of two recess environments and their impact on classroom attention after outdoor play. This research is important in understanding the impact recess has on classroom behavior. Recess environments were either on the playground or a nature walk. Preschool children were exposed to each of the recess environments for approximately 30 minutes per day for four weeks, and observational data were collected directly following each recess to determine the effects of outdoor activity on attention.
Color poster with text and graph.
Keywords: School recess breaks--Educational aspects; Playgrounds--Educational aspects; Attention in children--Environmental aspects; Posters